The contribution of rainfed rice farming to income and food security of farmers’ household - Arifin Arifin; Muhammad Arsyad Biba; Syafiuddin Syafiuddin (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
Increasing production from rainfed rice field farming is expected to have direct implications to farmers’ income and food security. Improvement in farmers’ income will ensure the fullfillment of quality food. This study aims to analyze the contribution of rainfed rice farming to the household income and household food security of the farmers who cultivate rice in rainfed rice fields. This research was conducted in Maros Regency in three districts, namely Lau, Maros Baru and Simbang. The sample of this research was 100 farmers in rainfed rice fields. The research used survey method with the instruments of observation, recording and interviews. Data were analyzed using quantitative description coupled with t-test for independent samples. The results showed that the rainfed rice farming contribution to the household income in Lau, Maros Baru and Simbang District was 90.0%, 70.0%, and 57.5%, respectively. In term of farm household food security based on the share of food expenditure, the farmers’ households were food insecure with 73.33%, 83.33%, and 67.50% for each regions. This study suggests that farmers need to diversify their income source to crops other than rice. Such effort will be able to increase the income and food security of farmers’ households.JEL Classification Q12; Q18; R14